The Lethality of [Pazopanib + HDAC Inhibitors] Is Enhanced by Neratinib - Booth, Laurence; Roberts, Jane L.; Poklepovic, Andrew; Dent, Paul (Frontiers in Oncology, 2019)
Sarcomas are a diverse set of malignancies. For soft tissue sarcomas, the kinase and chaperone inhibitor pazopanib is a standard of care therapeutic. Previously, we demonstrated that HDAC inhibitors enhanced pazopanib lethality against sarcoma and other tumor cell types in vitro and in vivo. The present studies defined mechanisms of drug-combination resistance. Exposure of sarcoma and PDX ovarian carcinoma cells to [pazopanib + entinostat] caused a prolonged activation of ERBB1 and transient/prolonged activations of ERBB2, c-KIT and c-MET, in a cell-specific fashion. The activities of mTORC1, mTORC2, GRP78, HSP90 and HSP70 were reduced, expression of Beclin1 and ATG5 enhanced, and the ATM-AMPK-ULK1-ATG13-Beclin1/ATG5 pathway activated. Inhibition of ERBB1/2/4 using neratinib or of c-MET using crizotinib significantly enhanced [pazopanib + entinostat] lethality. For neratinib with [pazopanib + entinostat], this effect correlated with reduced phosphorylation and expression of ERBB1, ERBB2, c-KIT and c-MET and reduced expression, regardless of mutational status, of N-RAS and K-RAS. [Pazopanib + entinostat + neratinib] reduced the phosphorylation of the Hippo pathway proteins MST1/3/4 and MOB1 whereas this treatment increased the phosphorylation of LATS1, YAP and TAZ. The activation of ATM, ULK-1 and eIF2 was further enhanced by [pazopanib + entinostat + neratinib] as was the expression of ATG5 and Beclin1. Compared to other manipulations, knock down of eIF2 or over-expression of BCL-XL significantly reduced killing by the three-drug interaction. In vivo, pazopanib and entinostat, and also neratinib and entinostat, both combined to significantly suppress the growth of sarcoma tumors.